Optimizing DSSCs Performance for Indoor Lighting: Matching Organic Dyes Absorption and Indoor Lamps Emission Profiles to Maximize Efficiency - Giorgia Salerno; Daniele Franchi; Alessio Dessì; Matteo Bartolini; Norberto Manfredi; Alessandro Abbotto; Ottavia Bettucci (ChemistryOpen, 2025)
Abstract The rapid proliferation of internet‐connected devices has transformed our daily habits prompting a shift towards greater sustainability in renewable energy for indoor applications. Among the various technologies available for obtaining energy in indoor conditions, Dye‐Sensitized Solar Cells (DSSCs) stand out as the most promising due to their ability to efficiently convert ambient light into usable electricity. This study explores how the optimal matching of the UV‐Vis absorption spectra of dyes commonly used in DSSCs with the emission profiles of indoor lamps allows for the enhanced efficiency of DSSC under indoor lighting. By testing four organic dyes with different UV‐Vis absorption spectra (L1, Y123, S1, and TP1) under two different common indoor light sources (OSRAM 930 and OSRAM 765 lamp), a significant dye‐lamp correlation was demonstrated. Notably, low‐priced dyes like S1 and TP1, characterized by easier synthetic routes and with an optimal overlap with the dye‐lamp spectrum, exhibited competitive efficiencies, narrowing the performance gap with high‐performing dyes like Y123, which require more demanding preparation approaches. The study highlights the critical importance of tailoring dye selection to specific indoor lighting environments, addressing a significant gap and paving the way for more sustainable and cost‐effective energy solutions for indoor applications.